A ampliação do ensino fundamental para nove anos e o ensino de leitura e escrita nos anos iniciais no município de São João - PR - Birch, Fabiana (2014)
This study has been developed from problematizations about the enlargement of Elementary Education (EE), to nine years lasting, referring to reading and writing teaching in the Early Years of learning. The aim was to analyze, with the teachers of 5th and 6th grades of this academic stage, in São João, PR, the relationships of this new organization of EE and the reading and writing learning process. The survey took place from 2012 to 2013 and involved all eleven state and municipal schools which offer 5th and 6th grades in this town. It was interviewed sixteen people with semistructured questions - six state teachers of Portuguese Language in the 6th grade, seven municipal teachers of the 5th grade (AIEF ), a municipal pedagogy teacher, the municipal secretary of education and the responsible for AIEF of nine years at Núcleo Regional de Pato Branco. The studied documents were the Pedagogical Proposition of schools for AIEF of the organization lasting eight and nine years of studying at elementary school in São João County; internal data of the institutions, referring to the ages and the scholar learning of Portuguese Language, the classes from 2011, 2012 and 2013, of 4th and 5th grades and 5th and 6th grades. The data were analyzed based on the assumptions of historical materialism as a theoretical-methodological approach that enabled a reflection upon a the research object, considering it in its entirety, relationships and contradictions, and historical and cultural assumptions of language studies, by Vygostki and Bakhtin, who understand the language as a social phenomenon, resulting from the cultural dimension of human experience and constituent subjects. The results of this study show that, with the implementation of Elentary Education of nine years lasting in the São João, the guidelines related to the adoption of learning cycles, as proposed for integral formation of students, received emphasis only in the first three AIEF grades , not contemplating the following grades (4th, 5th, 6th, 7th, 8th and 9th grades); there wasn´t reorganization of school content for classes of 5th grade; there wasn´t planning meetings between state and local teachers reported; and also there was no training for education professionals so it didn´t gave the support for schools and teachers to make the effective transition. This study also pointed improvement in students performance; changes on teachers' practices aiming a more contextualized and dynamic teaching, able to explore the textual diversity, with more time on reading and producing texts, than, specifically, the normative language teaching; inclusion of specific teaching content of literacy in the reorganized PPC; improved mastery of the written code with regard to the technical issues of writing students who arrive at 5th and 6th grades; and greater interest in reading. Such positive results in teaching and learning of reading and writing are situated in a historical context multidetermined and beyond the simple relation with the expansion of the time spent in school and its obligation, they may have been influenced by other programs and educational policies. However, the cultural-historical perspective that justified this search, it is recognized that when children get into school earlier, they have enlarged their possibilities of relations with the written culture and thus made possible the expansion of their learning.